Drug discovery in prostate cancer mouse models - Valkenburg, Kenneth C (Expert Opin Drug Discov, 2015)
INTRODUCTION: The mouse is an important, though imperfect, organism with which to model human disease and to discover and test novel drugs in a preclinical setting. Many experimental strategies have been used to discover new biological and molecular targets in the mouse, with the hopes of translating these discoveries into novel drugs to treat prostate cancer in humans. Modeling prostate cancer in the mouse, however, has been challenging, and often drugs that work in mice have failed in human trials. AREAS COVERED: Here we discuss similarities and differences between mice and men, types of mouse models that exist to model prostate cancer, practical questions one must ask when using a mouse as a model, and potential reasons that drugs do not often translate to humans. We will also discuss the current value in using mouse models for drug discovery to treat prostate cancer and what needs are still unmet in field. EXPERT OPINION: With proper planning and following practical guidelines by the researcher, the mouse is a powerful experimental tool. The field lacks genetically engineered metastatic models, and xenograft models do not allow for the study of the immune system during the metastatic process. There remain several important limitations to discovering and testing novel drugs in mice for eventual human use, but these can often be overcome. Overall, mouse modeling is an essential part of prostate cancer research and drug discovery. Emerging technologies and better and ever-increasing forms of communication are moving the field in a hopeful direction.